Listening Strategies in Sociolinguistic Interviews. Convergence and Divergence - Laforest, Marty (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1994)
Back-channel can be defined as tangible listening markers ("humhum," "yes," etc.) throughout a verbal interaction. In the Occident at least, completely silent listener-participation is unthinkable in conversations implicating two persons. In this study, I attempt to determine if convergence points in listening strategies among members of the same community exist, and to evaluate the margin of individual influence. To do this, I compare, within the same situation — the sociolinguistic interview — and considering a single type of discourse on the part of the informant — the narrative — the behaviour of several interviewers of the corpus Montreal 1984 at the level of both back-channel production frequency and of the contexts of the production of these signals.